Clinical and molecular cytogenetic analyses of four families with 1q21.1 microdeletion or microduplication. (April 2017) - Wang, Hong‐Dan; Liu, Lin; Wu, Dong; Li, Tao; Cui, Cun‐Ying; Zhang, Lian‐Zhong; Wang, Cheng‐Zeng
Abstract: Background: Little information is available regarding thepenetrance of 1q21.1 copy number variants (CNVs). In the present study, we explored the clinical significance of 1q21.1 microdeletion or microduplication. Methods: In four families, chromosome karyotype was analyzed using G‐banding karyotype analysis technology. CNVs were detected using array‐comparative genomic hybridization (aCGH) and then a quantitative polymerase chain reaction (qPCR) was used to validate candidate CNVs. Sequence signature in the breakpoint region was analyzed using University of California Santa Cruz (UCSC) databases. Results: Except for karyotype 45, XX, der (13, 14) (q10, q10) in the mother (I2) of family 2, the karyotype was normal in all other members of the four families. In the mother (I2) and fetus (II2) of family 1, in newborn (II1) of family 2 and in fetus (II1) of family 3, there was 1.22‐Mb heterozygous microdeletion in the chromosome 1q21.1q21.2 region. The child (II1) of family 4 had a 1.46‐Mb heterozygous microduplication in the chromosome 1q21.1q21.2 region. The results of the qPCR were consistent with that of aCGH. There was large number of low copy repeats (LCRs) in the breakpoint region found by analysis of the UCSC database, and multiple LCRs were matched with sequences in the chromosome 1 short‐arm region. Conclusions: 1q21.1 microdeletion and microduplication exhibit a variety of clinical manifestations and the specificity of their clinical features is not high. The penetrance of the distal 1q21.1 microdeletion may be affected by other factors in the present study. In summary, we report the discovery of a new distal 1q21.1 microduplication, which enriches the CNV spectrum in the 1q21.1 region and is conducive to prenatal genetic counseling.